Latin American Natural Product Database (LANaPDB): An Update - Gómez-García, Alejandro; Acuña Jiménez, Daniel A; Zamora, William J; Barazorda-Ccahuana, Haruna L; Chávez-Fumagalli, Miguel Á.; Valli, Marilia; Andricopulo, Adriano D; Bolzani, Vanderlan da S [UNESP]; Olmedo, Dionisio A; Solís, Pablo N; Núñez, Marvin J; Rodríguez Pérez, Johny R; et al. (American Chemical Society (ACS), 2024)
Natural product (NP) databases are crucial tools in computer-aided drug design (CADD). Over the past decade, there has been a worldwide effort to assemble information regarding natural products (NPs) isolated and characterized in certain geographical regions. In 2023, it was published LANaPDB, and to our knowledge, this is the first attempt to gather and standardize all the NP databases of Latin America. Herein, we present and analyze in detail the contents of an updated version of LANaPDB, which includes 619 newly added compounds from Colombia, Costa Rica, and Mexico. The present version of LANaPDB has a total of 13 578 compounds, coming from ten databases of seven Latin American countries. A chemoinformatic characterization of LANaPDB was carried out, which includes the structural classification of the compounds, calculation of six physicochemical properties of pharmaceutical interest, and visualization of the chemical space by employing and comparing two different fingerprints (MACCS keys (166-bit) and Morgan2 (2048-bit)). Furthermore, additional analyses were made, and valuable information not included in the first version of LANaPDB was added, which includes structural diversity, molecular complexity, synthetic feasibility, commercial availability, and reported and predicted biological activity. In addition, the LANaPDB compounds were cross-referenced to two of the largest public chemical compound databases annotated with biological activity: ChEMBL and PubChem.